(untitled) (Research, Society and Development, 2021)
This study has as its initial objective to investigate and present the results of research in an analytical way on the Digital Technologies of Information and Communication (TDICs): mediation teacher-student-content. With the intention of reaching the proposed objective, we tried to answer the problem: nowadays, with remote classes, how is the present, in the relation of TDICs: teacher-student-content, with a reality necessary for the Educational System fulfill your role with quality? Based on a bibliographic review, with a qualitative approach, the research will focus on issues that discuss Digital Information and Communication Technologies (TDICs), punctuating Teacher Education, Teacher-student-content Mediation, Active Methodologies and Narratives of Learning. Thus, a path of resignification of the teaching and learning process is outlined, with the use and appropriation of TDICs as mediation tools for learning and development, where literacies become the opportunity to scientifically literate.